Nonwoven polypropylene prosthesis in large abdominal wall defects in rats - Reis,Patrick dos Santos Barros dos (2012)
PURPOSE: To evaluate, in large abdominal wall defects surgically shaped in rats, if a synthetic polypropylene nonwoven prosthesis could be used as a therapeutic option to conventional polypropylene mesh. METHODS: Twenty four (24) Wistar rats were enrolled into three groups. Group 1 (Simulation group) with an abdominal wall defect of 3 X 3 left untreated and Groups 2 and 3, respectively treated with a conventional polypropylene mesh and a polypropylene nonwoven (NWV) prosthesis to cover the breach. At the 45th postoperatively day, adhesion (area and strength) and vascularization of Groups 2 and 3 were evaluated. The histological preparations with Hematoxylin-Eosin, Tricromium of Masson, Pricrosirius red and polarization with birefringence, and also the structural analysis of the prostheses carried on by Thermogravimetry and Differential Scanning Calorimetry were also assessed. RESULTS: There were no significant differences between the Groups 2 and 3. CONCLUSION: In rats, the polypropylene nonwoven prosthesis showed to be safe and has to be considered as an alternative to conventional mesh manufactured by weaving in the treatment of great defects of the abdominal wall.